2010
DOI: 10.3386/w16638
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Business Cycle Affect Eating Habits?

Abstract: As economic expansions raise employment and wages, associated shifts in income and time constraints would be expected to also impact individuals' health. This study utilizes information from the Behavioral Risk Factor Surveillance System (1990System ( -2007 to explore the relationship between the risk of unemployment and the consumption of various healthy and unhealthy foods. Estimates, based on fixed effects methodologies, indicate that a higher risk of unemployment is associated with reduced consumption of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 19 publications
5
43
1
Order By: Relevance
“…Both the UEFE during boom times and the 'enhanced UEFE' during crisis times are consistent with quality deterioration in diet during downturns with respect to boom periods. Dave and Kelly (2012) confirmed this relationship for US adults, finding a relationship between unemployment status and reduced consumption of healthy foods like fruit and vegetables. Herzfeld et al (2014) also reported the consumption of a less diversified diet by Russian households in regions with high unemployment rates.…”
Section: Results For the Average Treatment Effect On The Treated For supporting
confidence: 67%
“…Both the UEFE during boom times and the 'enhanced UEFE' during crisis times are consistent with quality deterioration in diet during downturns with respect to boom periods. Dave and Kelly (2012) confirmed this relationship for US adults, finding a relationship between unemployment status and reduced consumption of healthy foods like fruit and vegetables. Herzfeld et al (2014) also reported the consumption of a less diversified diet by Russian households in regions with high unemployment rates.…”
Section: Results For the Average Treatment Effect On The Treated For supporting
confidence: 67%
“…Recent evidence (Dave and Kelly 2010) suggests that individuals reduce their consumption of fruits and vegetables and substitute into relatively high-fat, high-calorie consumption during recessions.…”
Section: Discussionmentioning
confidence: 99%
“…Many papers examine the relationship between employment and unemployment indicators and health outcomes and behaviors (Ruhm 2000(Ruhm , 2003(Ruhm , 2005(Ruhm , 2007Bockerman et al 2007;Charles and DeCicca 2008;Arkes 2009;Dave and Kelly 2012). In addition, several papers have examined the effect of the business cycle on health-related time use channels (Burda and Hamermesh 2010; Aguiar et al 2013;Colman and Dave 2013a;Deb et al 2011).…”
Section: Introductionmentioning
confidence: 98%